Perbandingan Efisiensi Turbin Uap Kondisi Aktual Berbasis Data Komissioning Sesuai Standard ASME PTC 6 - Agus Noor Sidiq; Muhammad Anwar (KILAT, 2021)
The performance of steam turbine is very important to know and analyze to understand the actual condition compared to conditions of commissioning. The purpose of this paper is to understand the performance by comparing the efficiency of the steam turbine in actual conditions based on commissioning data in accordance with ASME PTC 6 rules. By doing this, it can be known the actual performance experienced by the steam turbine, the actual condition is what will be compared with the commissioning data so that later will be obtained performance differences that will be a concern in the continuous improvement of the steam turbine. The observations were made at Tarahan Power Plant Unit 3 regarding the condition of steam entering the turbine in this case the pressure and temperature, the condition of the extraction steam, and the condition of the exhaust side that will affect the performance analysis of the steam turbine.